Anodic Stripping Voltammetry of Se4+ on Gold-Modified Boron-Doped Diamond Electrodes. (26th July 2011) - Fierro, Stéphane; Watanabe, Takeshi; Akai, Kazumi; Yamanuki, Mikito; Einaga, Yasuaki
Abstract : Electrochemical detection of Se 4+ has been performed by anodic stripping voltammetry on a boron-doped diamond (BDD) electrode modified with gold nanoparticles deposited through chronocoulometry. This method is based on the affinity between the gold nanoparticles and Se 0, while the BDD electrode is presented as an ideal material for metal modification due to its unique properties. The resulting anodic stripping voltammograms exhibited a clear peak at 0.9 V versus AgCl related to Se 4+, and highly accurate (r 2 = 0.99 ) calibration curves could be obtained for a selenium concentration range between 10 and 100 μg/L. The influence of Se deposition time and other metals dissolved in solution (Cu, Cd, Pb, Cr, and B) has been investigated as well, and it was found that the Se 4+ calibration curves remained unaltered. For all the experiments performed, a detection limit around 10 μg/L was achieved. The high accuracy and reproducibility of the results as well as the excellent stability of the electrode material proves the excellent capabilities of this system for selenium detection.